Esmolol Use in Dual Axis Defibrillation Resistant Ventricular Fibrillation. (18th May 2020) - Agrawal, Ankit; Cardinale, Maria; Frenia, Douglas; Dalia, Tarun; Shah, Chirag
Abstract : Cardiac arrest in an event of acute myocardial infarction most commonly results in life-threatening ventricular tachycardia or ventricular fibrillation (VF). Patients who remain in VF despite optimal epinephrine, amiodarone, and three or more attempts at 200 joules of biphasic current defibrillation are known to be in an electrical storm. Here, we describe a case of defibrillation refractory VF responding to intravenous esmolol resulting in a successful return of spontaneous circulation. Learning objective . This case reinforces the growing body of evidence supporting esmolol as a novel treatment approach for refractory VF before the cessation of resuscitative efforts.